Control of motor coordination by transient receptor potential melastatin 8 through γ-aminobutyric acidergic circuit modulation in the male mouse cerebellum - Mayuka Koyama; Koki Harada; Naoko Takizawa; Shinji Kobuchi; Miwa Kambara; Hikaru Tanaka; Riona Araki; Yuri Yamada; Yukako Ito; Kazuyuki Takata; Shinichi Kato; Kenjiro Matsumoto (Scientific Reports)
Abstract Transient receptor potential melastatin 8 (TRPM8) is a non-selective cation channel that is activated by mild cooling and chemical agents. Although TRPM8 is widely expressed in the peripheral and central nervous systems, its cerebellar distribution and functional significance remain unexplored. We investigated the expression and role of TRPM8 in motor function using TRPM8-enhanced green fluorescent protein and TRPM8-deficient (TRPM8KO) mice. TRPM8 immunoreactivity was observed in parvalbumin- and vesicular γ-aminobutyric acid (GABA) transporter-labeled interneurons. TRPM8 was also expressed in hyperpolarization-activated cyclic nucleotide-gated potassium channel 1-labeled inhibitory plexuses that enveloped GABAA receptor-expressing Purkinje cell somata and terminated as pinceau. Next, motor functions were assessed in wild-type and TRPM8KO mice. TRPM8KO mice exhibited abnormal motor coordination in the rotarod test. However, TRPM8 deficiency did not affect body balance in the footprint test or general spontaneous activity in the open field test. To explore the importance of TRPM8 in motor coordination, the TRPM8 antagonist RQ-00203078 or vehicle (control) was intracerebrally or intraperitoneally administered; motor responses were analyzed using the rotarod test. Compared with vehicle, RQ-00203078 significantly reduced the rotarod retention time. Our results suggest that TRPM8 channels on inhibitory GABAergic neurons contribute to motor coordination by modulating synaptic transmission in Purkinje cell–interneuron synapses.